A New Molybdate-Based Inhibitor as a Replacement for Toxic Chromate Based Inhibitor in Cooling Water System - KARAMINEZHAAD, M.; BAGHAEI RAVARI, F.; DADGARYNEZHAD, A.; KAVIANPOOR, Y. (Asian Journal of Chemistry, 2010)
Molybdate-based inhibitor is long known as an inorganic type inhibitor and is less toxic than chromate-based inhibitors, which are used in cooling water systems. Electrochemical techniques were used to study the inhibition effects on the general and pitting/crevice corrosion of mild steel, which is the main alloy of cooling water systems: In this study a molybdate-based inhibitor has been introduced with the composition of 40 ppm molybdatel15 ppm phosphate/40 ppm polyphosphate/10 ppm zinc. It has been compared with a low chromate and a commercial inhibitor. To study the inhibition effects of inhibitors on the uniform and pitting corrosion of mild steel, electrochemical techniques such as potentiodynamic, polarization and cyclic polarization, weight loss method and surface analysis techniques such as SEM and EDS microanalysis have been used. The results indicate that this molybdate-based inhibitor is as effective as the low chromate inhibitor and it is more effective than the commercial one.